Implementation of School Principal's Leadership Management on Teacher Performance in Improving Academic Achievement of Madrasah Ibtidaiyah Students - Fauji, Rizal; Misriandi; Sofian Hadi, Muhamad (Global Action and Education for Society, 2025)
This study aims to describe and analyze the implementation of school principal leadership management in improving teacher performance and enhancing students’ academic achievement at Madrasah Ibtidaiyah (MI) in Pamijahan District. The research employed a qualitative approach with a case study method involving six madrasahs selected purposively. Data collection techniques included in-depth interviews, classroom observations, and document analysis. The principal findings reveal that school principals play strategic roles as managers, supervisors, motivators, and educational leaders in optimizing teacher performance. Key leadership management practices include participatory planning, systematic task organization, professional development through continuous training, classroom supervision, and performance evaluations based on student learning outcomes. Teacher performance improvement was evidenced by more structured lesson planning, diversified teaching methods, and better classroom management. Consequently, students’ academic achievements showed significant improvement, indicated by increased attainment of minimum learning standards and active participation during lessons. Nevertheless, principals encountered challenges such as limited learning facilities and varied teacher motivation levels. These obstacles were addressed through collaborative strategies involving school committees and continuous professional development programs. Overall, effective leadership management from principals significantly contributes to enhancing teacher competence and student academic outcomes. This study underscores the vital role of transformational leadership in Islamic primary education, providing practical recommendations for school management development at the madrasah level. The findings also highlight the necessity of strengthening principal training programs and institutional support to ensure sustainable quality improvement in basic Islamic education.